The complex interplay in the regulation of cardiac pathophysiologic functionalities by protein kinases and phosphatases - Sr, Chrysanthus Chukwuma (Journal of Cardiology and Cardiovascular Medicine, 2021)
Protein phosphorylation regulates several dimensions of cell fate and is substantially dysregulated in pathophysiological instances as evident spatiotemporally via intracellular localizations or compartmentalizations with discrete control by specific kinases and phosphatases. Cardiovascular disease manifests as an intricately complex entity presenting as a derangement of the cardiovascular system. Cardiac or heart failure connotes the pathophysiological state in which deficient cardiac output compromises the body burden and requirements. Protein kinases regulate several pathophysiological processes and are emerging targets for drug lead or discovery. The protein kinases are family members of the serine/threonine phosphatases. Protein kinases covalently modify proteins by attaching phosphate groups from ATP to residues of serine, threonine and/or tyrosine. Protein kinases and phosphatases are pivotal in the regulatory mechanisms in the reversible phosphorylation of diverse effectors whereby discrete signaling molecules regulate cardiac excitation and contraction. Protein phosphorylation is critical for the sustenance of cardiac functionalities. The two major contributory ingredients to progressive myocardium derangement are dysregulation of Ca2+ processes and contemporaneous elevated concentrations of reactive oxygen species, ROS. Certain cardiac abnormalities include cardiac myopathy or hypertrophy due to response in untoward haemodynamic demand with concomitant progressive heart failure. The homeostasis or equilibrium between protein kinases and phosphatases influence cardiac morphology and excitability during pathological and physiological processes of the cardiovascular system. Inasmuch as protein kinases regulate numerous dimensions of normal cellular functions, the pathophysiological dysfunctionality of protein kinase signaling pathways undergirds the molecular aspects of several cardiovascular diseases or disorders as related in this study. These have presented protein kinases as essential and potential targets for drug discovery and heart disease therapy.